On the resolution of a long standing issue surrounding the holotype of Cnemaspis podihuna Deraniyagala, 1944 (Reptilia: Gekkonidae) - Amarasinghe, A.a. Thasun; Campbell, Patrick D. (Zootaxa, 2016)
The number of species in the genus Cnemaspis Strauch, 1887 has grown rapidly, and it currently comprises more than 100 species (Grismer et al. 2014; Amarasinghe et al. 2015). The Sri Lankan endemic and vulnerable day-gecko Cnemaspis podihuna Deraniyagala, 1944 (Ministry of the Environment 2012) was first described by Deraniyagala from the Lahugala-Maha Oya, Eastern Province on the basis of one holotype and four paratypes [incorrectly reported as three paratypes by Karunarathna et al. 2010]. There had been no further collections or sightings made of this species until Wickramasinghe (2000) rediscovered the species from Koslanda in the Badulla District (National Museums of Sri Lanka, Colombo, NMSL RG 21a–e). Wickramasinghe and Munindradasa (2007) collected a further four specimens (NMSL 20061001–4) around the type locality. Recently, Sri Lankan members of the day-gecko genus Cnemaspis were reviewed and redescribed morphologically by two groups of researchers: Wickramasinghe and Munindradasa (2007) and Manamendra-Arachchi et al. (2007). The former group considered the holotype lost. Therefore, they designated a neotype plus syntypes for C. podihuna. This action was invalidated by Pethiyagoda (2007) following the International Code of Zoological Nomenclature (ICZN 1999).